The Buddhist Ethical Foundations of Animal Rights: Scriptural Teachings and Contemporary Practices - Medhacitto, Tri Saputra (LPPM STIAB JINARAKKHITA LAMPUNG, 2025)
This paper explores the ethical foundations of animal rights from a Buddhist perspective, focusing on the fundamental teaching of non-violence (ahiṃsā), lovingkindness (mettā) and compassion (karuṇā). Grounded in the Buddha's teaching as reflected in the Pāli Canon and its commentaries, Buddhism advocates non-violence, lovingkindness and compassion to all living beings, including animal. The principle of Ahiṃsā calls for abstention from causing harm or killing to animals. Mettā promotes the cultivation of lovingkindness, an active intention and action for the welfare of others, to all living beings. Karuṇā encourages a compassionate action and active response to reduce the suffering of all living beings. Through these ethical principles, Buddhism provides a moral basis for advocating the respectful and compassionate treatment towards animals. Furthermore, it discusses the emergence of modern Buddhist movements who promote compassionate living through practices such as fang sheng (animal release), establishing animal sanctuaries, avoiding meat, rejecting products like leather and silk, and replacing animal labor with machines.